LEGAL STUDY ON RUISLAGH OF WAQF LAND WHICH IS AFFECTED BY THE DEVELOPMENT OF PUBLIC FACILITIES ON THE MAQASHID SHARIA PERSPECTIVE - ANI YUMARNI; MULYADI MULYADI; SITI MARYAM (Universitas Islam Negeri Imam Bonjol Padang, 2022)
This article provides an explanation and disclosure of the implementation of the Transferring Function (ruislagh) of waqf land that is not in accordance with the laws and regulations. Looking back at the philosophical aspects of Islamic law by using the maqashid sharia perspective. The method used is a qualitative method using a normative juridical approach. This paper examines the principles, concepts of waqf law, legal provisions for management and transfer of waqf land functions. On the maqashid sharia perspective, the exchange of waqf property can be done as long as it met the benefits and basic needs are fulfilled through the choice of transferring function. Public cemeteries, public roads, the provision and expansion of educational facilities, and other forms of designation, in the context of Islamic law are seen as objects that are the main needs of the community. So that in order to fulfill basic needs and achieve maqashid sharia, the exchange of waqf property (ruislagh) can be held.